Numerical analysis of toroidal voids as stress relievers in shrink-fitted shafts. (March 2020) - Erena, D.; Vázquez, J.; Navarro, C.; Domínguez, J.
Abstract: High stress concentrations, slip and wear appear in shrink-fitted shafts near the contact edge in operational conditions. Due to these high stresses, and time fluctuation nature of the loads supported by shafts, cracks rapidly initiate at this surface location. This combination of events is known as fretting fatigue, which is a damage phenomenon produced in many mechanical joints. Several solutions to increase fretting fatigue life are found in practice, they include the introduction of compressive residual stresses or the reduction of stresses through a geometry modification, e.g., a slot in the shaft outside of the contact, an increase of the shaft's diameter in the contact zone, etc. This paper suggests a new geometry modification based on an increasingly popular technique that allows the manufacturing of pieces of difficult shapes, and nearly impossible to make with other techniques: additive manufacturing (AM). The idea is to introduce an internal void in the shaft, with a toroidal shape and beneath the contact edge. This feature makes the void surrounding zone more flexible, thus, reducing the contact stress field near the contact edge zone. Several geometrical configurations are numerically studied, concluding that, there is an optimal position of the void that produces, in terms of a multiaxial fatigue parameter, a significant decrease of the fatigue damage on the interest zone. Highlights: Analysis of voids as fretting fatigue palliative in shrink-fitted shafts. Different voids size, position and loading conditions are numerically analysed. Decreases in terms of a multiaxial damage parameter are observed.